The Development of a User Feedback Management Process: A Participatory Action Research Project - Tang, David Li; Bouthillier, France; Pluye, Pierre; Grad, Roland; Repchinsky, Carol (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This poster presents the methodology of a doctoral dissertation project in progress. The objective of the project is to understand the factors involved in developing a user feedback management process. This project is part of a Participatory Action Research (PAR) with the Canadian Pharmacists Association (CPhA). Cette affiche présente la méthodologie d’une étude doctorale en cours. L’objectif du projet est de comprendre les facteurs importants dans le développement d’un processus de gestion de la rétroaction des usagers. Ce projet s’inscrit dans le cadre d’une recherche-action participative avec l’Association des pharmaciens du Canada (APhC).